Pengambilan Keputusan Penentuan Sentra Industri Kecil dan Menengah Unggulan Menggunakan Metode Analytical Hierarchy Process (AHP) - Fawait, Aldi Bastiatul; Yudhana, Anton; Umar, Rusydi (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2022)
The analysis process for determining Small and Medium Industry (IKM) centers to produce IKM that are able to develop and excel in the era of the COVID-19 pandemic in the City of Yogyakarta. Determination of leading IKM plays an important role in creative and innovative industries. However, there are still many unresolved IKM decisions that are made manually, which makes the process long and inefficient. The entry of technology into various disciplines makes the process of determining the leading IKM more efficient and systematic. To facilitate the determination of leading IKM, you can use the Decision Support System (DSS), where the author in conducting the analysis applies the Analytical Hierarchy Process (AHP) method which can facilitate the determination of IKM by determining the weight of the selected criteria. The results showed that the consistency ratio value was 0,0961 or < 0,1 which from the calculation results can be interpreted as correct based on the CR arithmetic theory in the AHP method and is feasible to use. This study resulted in a ranking of the leading IKM centers, namely alternative A9 in 1st, A3 in 2nd, A2 in 3rd, A8 in 4th, A5 in 5th, A1 in 6th, A10 in 7th, A7 in 8th, A4 in 9th and A6 in 10th. The results of the study found that the AHP method could be used for decision making in determining the leading IKM centers.